Early primary biliary cholangitis is characterised by brain abnormalities on cerebral magnetic resonance imaging. Issue 9 (8th September 2016) - Grover, V. P. B.; Southern, L.; Dyson, J. K.; Kim, J. U.; Crossey, M. M. E.; Wylezinska‐Arridge, M.; Patel, N.; Fitzpatrick, J. A.; Bak‐Bol, A.; Waldman, A. D.; Alexander, G. J.; Mells, G. F.; et al.
Summary: Background: Brain change can occur in primary biliary cholangitis (PBC), potentially as a result of cholestatic and/or inflammatory processes. This change is linked to systemic symptoms of fatigue and cognitive impairment. Aim: To identify whether brain change occurs early in PBC. If the change develops early and is progressive, it may explain the difficulty in treating these symptoms. Methods: Early disease brain change was explored in 13 patients with newly diagnosed biopsy‐proven precirrhotic PBC using magnetisation transfer, diffusion‐weighted imaging and 1 H magnetic resonance spectroscopy. Results were compared to 17 healthy volunteers. Results: Cerebral magnetisation transfer ratios were reduced in early PBC, compared to healthy volunteers, in the thalamus, putamen and head of caudate with no greater reduction in patients with greater symptom severity. Mean apparent diffusion coefficients were increased in the thalamus only. No 1 H magnetic resonance spectroscopy abnormalities were seen. Serum manganese levels were elevated in all PBC patients, but no relationship was seen with imaging or symptom parameters. There were no correlations between neuroimaging data, laboratory data, symptom severity scores or age. Conclusions: This is the first study to be performed in this precirrhotic patient population, and we have highlighted that neuroimaging changes are present at a much earlier stage than previously demonstrated. The neuroimaging abnormalities suggest that the brain changes seen in PBC occur early in the pathological process, even before significant liver damage has occurred. If such changes are linked to symptom pathogenesis, this could have important implications for the timing of second‐line‐therapy use.